STUDENT MISCONCEPTION ON REDOX TITRATION (A CHALLENGE ON THE COURSE IMPLEMENTATION THROUGH COGNITIVE DISSONANCE BASED ON THE MULTIPLE REPRESENTATIONS) (Jurnal Pendidikan IPA Indonesia, 2016)
The misconception is one of the obstacles in the concept mastery that needed to be minimalized. This descriptive study was conducted to find the patterns of misconceptions which have occurred on college students who participating in the redox titration course subject. Efforts to minimize misconceptions have been conducted through lectures using the multiple representations with the cognitive dissonance strategies on the 30 students who joined the Fundamentals of Analytical Chemistry course. The research instrument used in this study was 6 multiple-choice tests with reasons. In order to detect the misconception, Certainty of Response Index technique was performed. The preliminary study results showed that 34.30% of students experiencing the misconceptions on redox titration. After treatments, the misconceptions reduced to 28.17%. A misconception that cannot be eliminated was related to the concepts involving in the microscopic and symbolic appearances.